EGF rs11568835 G/A polymorphism is associated with increased risk of rheumatoid arthritis. (November 2014) - Wang, Liqun; Bo, Lin; Yan, Ting; Zhang, Hui; Zhou, Guoxin; Liu, Ruiping
Abstract Rheumatoid arthritis (RA) is an autoimmune rheumatological disease thought to have substantial genetic contributions. Epidermal growth factor (EGF) can activate DNA synthesis and cellular proliferation. Early RA synovial fluid was characterized by significantly elevated levels stromal cell and macrophage-related cytokines including EGF. We therefore hypothesized that EGF polymorphisms may contribute to RA susceptibility in the Chinese population. We studied EGF rs11568835 G/A and EGF rs3756261 T/C polymorphisms in 520 patients with RA and 520 controls in a Chinese population. When the EGF rs11568835 GG homozygote genotype was used as the reference group, the AA genotype was associated with an increased risk for RA (AA versus GG, odds ratio [OR] = 3.64, 95% confidence interval [CI] = 1.19–11.17, p = 0.024), the GA or GA/AA genotype was not associated with the risk for RA (GA versus GG, OR = 0.99, 95% CI = 0.75–1.31, p = 0.931; GA + AA versus GG, OR = 1.06, 95% CI = 0.81–1.40, p = 0.659). EGF rs3756261 T/C was not associated with susceptibility to RA. These results provide the first positive evidence for an association between EGF rs11568835 G/A polymorphism and RA.